1984
DOI: 10.1002/lsm.1900040411
|View full text |Cite
|
Sign up to set email alerts
|

Biological effect of He‐Ne laser: Investigations on functional and micromorphological alterations of cell membranes, in vitro

Abstract: A 1-J/cm2 dose of single laser-irradiation applied on primary human embryo fibroblast culture was not followed either by functional or micromorphological alterations of cell surfaces. This dose, however, applied four times with 24-hour intervals changed the functional conditions as well as surface charges of cell membranes. As detection methods, radioactive glucosamine uptake, lectin, and cationized ferritin-binding techniques were applied. At the same time, the scanning and transmission electron microscopy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
6

Year Published

1985
1985
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(22 citation statements)
references
References 8 publications
0
16
0
6
Order By: Relevance
“…Other low energy laser irradiation experiments on cell cultures in vitro have been performed mainly on fibroblasts (Bosatra et al, 1984;Kubasova et al, 1984;Balboni et al, 1986;Boulton & Marshall, 1986;Lam et al, 1986;Glassberg et al, 1988;Pourreau-Schneider et aI., 1990), but also on HeLa cells (Karu et al, 1984), E. coli (Karu et aI., 1983), and lymphocytes (Passarella et al, 1985;Meyers et al, 1987;Fedoseyeva et al, 1988;Inuoe et aI., 1989;Manteifel et al, 1991). In most of these experiments similar modulatory effects of laser irradiation on cell proliferation were seen.…”
Section: Discussionmentioning
confidence: 99%
“…Other low energy laser irradiation experiments on cell cultures in vitro have been performed mainly on fibroblasts (Bosatra et al, 1984;Kubasova et al, 1984;Balboni et al, 1986;Boulton & Marshall, 1986;Lam et al, 1986;Glassberg et al, 1988;Pourreau-Schneider et aI., 1990), but also on HeLa cells (Karu et al, 1984), E. coli (Karu et aI., 1983), and lymphocytes (Passarella et al, 1985;Meyers et al, 1987;Fedoseyeva et al, 1988;Inuoe et aI., 1989;Manteifel et al, 1991). In most of these experiments similar modulatory effects of laser irradiation on cell proliferation were seen.…”
Section: Discussionmentioning
confidence: 99%
“…ported in Wobarsht, demonstrated accelerated growth of somatic nerves with exposure to He-Ne laser radiation (1 7). Kubasova et al (6) found that a 1-J/cm2 dose of He-Ne laser radiation applied four times at 24-hour intervals changed the firnctional conditions as well as surface charges of embryonic cell membranes, which is consistent with stimulation of epithelization (6). Walker and Akhan-jee (1 5 ) , as a result of their study on laser-induced soniatosensory evoked potentials, believe the peripheral nervous system possesses a previously unsirspected degree of photosensitivity, which may provide rationale for therapeutic applications of lowpower laser.…”
Section: Of the Crushed Peroneal Nervementioning
confidence: 96%
“…Laser irradiation has a demonstrable effect in vitro on both metabolism and surface charges on cells in culture, but the ultra-structure is unchanged [40]. Research studies of the effects of low power laser irradiation on biological functioning, are growing in number and scope.…”
Section: Discussionmentioning
confidence: 99%